Therapy in Advanced Hepatocellular Carcinoma - Javan, Hanna; Dayyani, Farshid; Abi-Jaoudeh, Nadine (Seminars in Interventional Radiology, 2020)
Treatment of advanced hepatocellular carcinoma (HCC) is challenging. Several randomized clinical trials are investigating the efficacy of systemic therapy, immunotherapy, and locoregional therapy as monotherapy or combined with other modalities in the treatment of HCC. Systemic therapy is the preferred treatment in advanced disease. To date, multiple first-line and second-line agents received Food and Drug Administration approval. For over a decade, sorafenib was the only first-line agent. In May 2020, combination of atezolizumab and bevacizumab has been approved as a first-line systemic regimen. Lenvatinib is another first-line agent that has multikinase activity. Second-line agents include cabozantinib, regorafenib, ramucirumab, and nivolumab. Adoptive cell transfer therapy is a highly specific immunotherapy that has shown antitumor activity against HCC. Oncolytic viruses are genetically modified viruses that infect cancer cells and induce apoptosis. Locoregional therapies such as transarterial chemoembolization and radioembolization have shown a potential benefit in selected patients with advanced HCC. In this review, we aim to summarize the treatment options available for advanced HCC.
Keywords: hepatocellular carcinoma; systemic therapies; locoregional therapies